Anakinra to Mitigate Hemophagocytic Lymphohistiocytosis-Like Toxicity Following Chimeric Antigen Receptor T-cell Therapy in Pediatric B-cell ALL - Na Yoon Lee; Suejung Jo; Jae Won Yoo; Seongkoo Kim; Jae Wook Lee; Nack-Gyun Chung; Bin Cho (The Korean Society of Pediatric Hematology-Oncology, 2022)
Hemophagocytic lymphohistiocytosis-like toxicity following chimeric antigen receptor (CAR)-T cell therapy (carHLH) is a rare and fulminant complication. Currently, there are neither well-established diagnostic criteria nor optimal treatment option for carHLH. Given the similarities of hyperinflammatory process and cytokine profiles between cytokine release syndrome (CRS) and carHLH, tocilizumab and corticosteroids are the suggested front-line treatment options for both conditions. However, when carHLH is refractory to front-line treatment, alternative or adjunctive agents should be introduced to ameliorate ongoing hyperinflammation. Anakinra, a recombinant interleukin (IL)-1 receptor antagonist, has shown promising results in the management of carHLH. Although prospective trials are limited, the use of anakinra for severe CRS and carHLH has been increasing. In this case report, we present two cases of carHLH to discuss its characteristic clinical features, diagnostic criteria, and treatment option. In addition, we also highlight the clinical efficacy of anakinra for managing carHLH which was refractory to tocilizumab and dexamethasone.